Rearranged T Cell Receptor Sequences in the Germline Genome of Channel Catfish Are Preferentially Expressed in Response to Infection - Findly, Robert Craig; Niagro, Frank D.; Sweeney, Ryan P.; Camus, Alvin C.; Dickerson, Harry W. (Frontiers in Immunology, 2018)
Rearranged V(D)J genes coding for T cell receptor α and β chains are integrated into the germline genome of channel catfish. Previous analysis of expressed TCR Vβ2 repertoires demonstrated that channel catfish express multiple public clonotypes, which were shared among all the fish, following infection with a common protozoan parasite. In each case a single DNA sequence was predominately used to code for a public clonotype. We show here that the rearranged VDJ genes coding for these expressed public Vβ2 clonotypes can be amplified by PCR from germline DNA isolated from oocytes and erythrocytes. Sequencing of the Vβ2 PCR products confirmed that these expressed public Vβ2 clonotypes are integrated into the germline. Moreover, sequencing of PCR products confirmed that all five Vβ gene families and Vα1 have rearranged V(D)J genes with diverse CDR3 sequences integrated into the germline. Germline rearranged Vβ2 and Vβ4 genes retain the intron between the leader and Vβ sequence. This suggests that the germline rearranged TCR Vβ genes arose through VDJ rearrangement in T cells, and subsequently moved into the germline through DNA transposon mediated transposition. These results reveal a new dimension to the adaptive immune system of vertebrates, namely: the expression of evolutionarily conserved, rearranged V(D)J genes from the germline.